Ultrasonically Assisted Efficient and Green Protocol for the Synthesis of Bisindolylmethanes Using Malic Acid as a Homogeneous and Reusable Organocatalyst - Kasar, Sandeep B.; Thopate, Shankar R. (Current Green Chemistry, 2018)
Background: Bis(indolyl)methane, indole and their derivatives are known as vital intermediates in the pharmaceutical chemistry and organic synthesis which exhibits a range of physiological properties. Bis(indolyl)methanes are found in cruciferous plants and are well known to promote beneficial estrogen metabolism and induce apoptosis in human cancer cells. Bis(indolyl)methanes have received much attention in recent years. A major source of waste in the (fine) chemicals industry is derived from the widespread use of liquid mineral acids (HF, H2SO4) and a variety of Lewis acids. They cannot be easily recycled and generally end up as waste containing large amounts of inorganic salts. Their widespread replacement by recyclable solid acids such as malic acid, tartaric acid and malonic acid etc., which are naturally occurring, would afford a dramatic reduction in waste. Thus there is need to find out green protocols for the synthesis of bioactive molecules. Objective: To develop green protocol for the synthesis of bisindolylmethane derivatives. Methods: Bisindolylmethane derivatives were synthesized in 85-95 % by using ultrasonication technique in presence of malic acid as an organocatalyst in water as a green solvent at ambient reaction condition. Results: We have demonstrated that malic acid can be used as a benign organocatalyst for organic transformations with high efficacy and excellent reusability. Conclusion: In conclusion, we have developed ultrasonically assisted malic acid catalyzed metal free green protocol for the bis(indolyl)methanes under homogenous conditions. The notable advantages of this method are the use of water as a green solvent, efficient eco-friendly and inexpensive catalyst, ambient temperature and high reusability of the catalyst. Therefore, this protocol can be a promising alternative to the use of Lewis and mineral acid catalysed organic reactions. Further studies of exploiting the efficiency of naturally occurring acids as a green catalyst in synthesis of various heterocyclic compounds are in progress.
Keywords: malic acid